Chemical deposition of CdS films from ammoniac-thiourea solutions - Pancheva, Hanna; Khrystych, Olena; Mykhailova, Evgeniia; Ivashchenko, Maryna; Pilipenko, Alexei (Технологический центр, 2018)
This paper investigates the process of chemical deposition of CdS films from ammonia-thiourea solutions. It was established that a change in the turbidity of solution occurs in the process of chemical deposition. The results of visual observations and measurement of turbidity of solution allowed us to establish that these dependences could be used to monitor the status of the process. Visual observations correlate with the obtained dependences for turbidity and suggest that the chemical deposition of CdS includes the accumulation of colloidal-dispersed precipitate in the volume of solution, agglomeration of CdS particles, and a stationary mode of the CdS film growth at the surface of a sample. The first stage of the process is matched by a sharp increase in the turbidity of solution; the second stage is accompanied by the emergence of a maximum in the dependence. No significant change in turbidity occurs at the third stage. The observation of morphology of the resulting precipitate allowed us to establish working concentrations of reagents in solution, which ensure obtaining a high-quality CdS film with a thickness not less than 100 μm. The working concentrations of cadmium chloride, ammonia, and thiourea are, respectively, 1.8, 0.6, and 8.4 g·l⁻¹. It was assumed that the CdS formation is accompanied by the formation of thiourea. This is confirmed by data on the analysis of a working solution. An analysis of the solution revealed high concentrations of the CO₃²⁻ ions, which are a product of the thiourea decomposition. The data obtained are a preliminary stage in the development of a technology of chemical deposition of CdS films from ammonia-thiourea solutions.

Досліджений вплив концентрації реагентів на зміну мутності в процесі хімічного осадження плівок сульфіду кадмію з аміачнотіокарбамідних розчинів. За результатами досліджень зміни мутності розчинів в процесі осадження та морфології одержаного осаду визначені концентрації CdCl₂, NH₄OH і CS(NH₂)₂ при яких утворюється суцільна плівка CdS. Проведена робота дозволила встановити умови формування суцільних плівок CdS, що є передумовою для розробки контрольованого процесу виготовлення фотоелектричних перетворювачів.
Keywords: photoelectric converters; cadmium sulfide; chemical deposition; turbidity; ammoniac-thiourea solutions; фотоелектричні перетворювачі; сульфід кадмію; хімічне осадження; мутність; аміачнотіокарбамідні розчини